PEMETAAN KEBUTUHAN DAN PENGGUNAAN MEDIA PEMBELAJARAN 3D DI SEKOLAH DASAR KECAMATAN ILIR TIMUR II PALEMBANG - Wayan Arya Sugiarnawo (Universitas Katolik Musi Charitas, 2019)
The background of this research is the limited use of media in teaching and learning in schools. This study is entitled